GRAPHIC DESIGN AND (GUERILLA MARKETING) - ÖZDEMİR, Abdulkadir (Atlas Journal, 2021)
Abstract Graphic Design and Advertising is one of the most common advertising techniques with increasing importance and influence day by day. In researches, Guerilla Marketing advertising technique and graphic design, which started in the 1980s and were very effective in terms of advertising, were examined and their effects on product promotions were investigated, designs were analyzed and examples were given. "Communication", which is as old as the history of humanity, is still effective today. Advertising and design are inseparable parts, two complementary phenomena. Advertising and design are used in every field from political parties to the smallest firm, whether or not people are aware of it, they constantly encounter advertisements and designs on the radio, television, newspapers, magazines, billboards, etc. Guerilla Marketing technique has attracted attention when it has achieved different and rapid growth and it is a promotional tool that has been applied by every company. It was first applied by Jay Conrad Levinson to help large and small companies compete. J. Conrad Levinson called this marketing technique "Guerilla Marketing-Advertising". Guerrilla Marketing technique is a more economical, fast reaching and effective method. Guerilla Marketing technique is a phenomenon that requires imagination and design.